Integrating Artificial Intelligence into Interior Design Education: A Case Study on Creating Office Spaces for “Avrupa Yakası” TV Series Characters - M. Uğur Kahraman; Yaren Şekerci; Müge Develier (Interaction Design and Architecture(s), 2023)
The integration of artificial intelligence (AI) into interior design education is a growing trend. This study presents a warm-up assignment where students used AI design tools to develop a concept of contemporary office designs inspired by characters from the TV series “Avrupa Yakası.” The goal was to prepare students for an office design project while introducing them to AI applications. The AI-generated designs reflected character personalities and aesthetic preferences. Findings show the AI’s capability to translate textual cues into visual designs, but limitations arise due to insufficient definitions in the AI’s memory. The study highlights AI’s potential for assisting in design inspiration but also emphasizes the need for continuous AI database development. This initiative contributes to understanding AI’s role in design education and its evolving impact on creative processes.